MENYIBAK AGENCY PROBLEM PADA KONTRAK MUDHARABAH DAN ALTERNATIF SOLUSI - Maharani, Satia Nur (Jurnal Keuangan dan Perbankan, 2008)
Islamic Banking has been established is almost every part in the world. Mudharabahand musyarakah are two contracts which mainly characterize syariah banks. Mudharabah isthe clearest differing characteristic as well as positioning for syariah banks in competingconventional banks. Unfortunately, mudharabah and musyarakah are still rarely practiced.Risk averse attitude which is shown by syariah banking is caused by the information asymmetryand moral hazard by mudharib or clients, especially in terms of profit reporting. The informationasymmetry and moral hazard are triggers of agency problem.